Assistance in Reading the Al-Quran to Increase Motivation and Interest Student of TPQ As Salma Maronde: Pendampingan Membaca Al-Quran untuk Meningkatkan Motivasi dan Minat Santri TPQ As Salma Maronde - Syam, Nur; Syamsunardi, Syamsunardi; Syarif, Erman; Hastati, Sri; Jumriani, Jumriani (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Assistance in reading the Al-Quran is a service to the community as an effort to implement the tri dharma of higher education. This is done to increase students' motivation and interest in reading the Al-Quran. The learning assistance method used is to provide direct learning assistance, namely community service program implementers, Ustadzah and students reading the Al-Quran directly and face to face. Assistance in reading the Al-Quran was carried out at TPQ As Salma Maronde. The mentoring process carried out went well and smoothly. The results obtained from assistance in reading the Al-Quran at TPQ As Salma Maronde are as follows: 1) Increasing motivation and interest in reading the Al-Quran for TPQ As Salma Maronde students, 2) Providing direct assistance to TPQ As Salma Maronde students in reading and writing Al- Quran, 3) Assistance in reading the Al-Quran is fun and can increase the motivation of the students. Abstrak Pendampingan membaca Al-Quran ini merupakan pengabdian kepada masyarakat sebagai upaya pelaksanaan tri dharma perguruan tinggi. Hal ini dilakukan untuk meningkatkan motivasi serta minat santri membaca AlQuran. Metode pendampingan belajar yang digunakan dengan memberikan pendampingan belajar secara langsung, yakni para pelaksana program pengabdian kepada masyarakat, Ustadzah dan santri membaca Al-Quran secara langsung dan tatap muka. Pendampingan membaca Al-Quran ini dilakukan di TPQ As Salma Maronde. Proses pendampingan yang dilakukan berjalan dengan baik dan lancar. Hasil yang diperoleh dari pendampingan membaca Al-Quran di TPQ As Salma Maronde sebagai berikut: 1) Meningkatkan motivasi dan minat membaca Al-Quran santri TPQ As Salma Maronde, 2) Pemberian pendampingan langsung kepada santri TPQ As Salma Maronde dalam baca dan tulis Al-Quran, 3) Pendampingan membaca AlQuran terasa menyenangkan dan dapat meningkatkan motivasi para santri.